ANALISA EFISIENSI PERFORMA HRSG ( Heat Recovery Steam Generation ) PADA PLTGU - Bambang Setyoko (TRAKSI, 2006)
Heat Recovery Steam Generator ( HRSG ) is a construction in combine cycle with gas turbine and steam turbine. The steam produced in HRSG with heat from exhaust gas turbine. In this research we can calculate HRSG efficiency to compare total energy  heat flow for steam produce from feed water and total energy heat flow from exhaust gas turbine. The result of this calculate research are optimal efficiency 54,04 % with total energy superheated steam heat  flow 132,91 MW, total energy exhaust gas turbine 245,953 MW and minimum efficiency 50,39 % with total energy superheated steam heat flow 124,788 MW, total energy exhaust gas turbine 247,64 MW.Key words : exhaust gas,steam, heat flow.